Ottoman-Southeast Asian relations : sources from the Ottoman Archives - Kadi, Ismail Hakki; Peacock, A. C.; Casale, Giancarlo (Leiden ; Boston : Brill, 2020)
c
Includes bibliographical references and index.
Documents and text in English, Arabic, Burmese, French, Malay, Ottoman-Turkish, Tausug, and Thai.
Keywords: Turkey -- Relations -- Southeast Asia -- Sources; Southeast Asia -- Relations -- Turkey -- Sources; Turkey -- History -- Ottoman Empire, 1288-1918 -- Sources; Southeast Asia -- History -- Sources